Potential Risk Posed by Meat and Unprocessed Milk in the Transmission of Brucellosis in Eldoret Municipality, Kenya - H.A. , Rachuonyo; J.K , Rotich; D.K. , Kios; S.W. , Kim; J.W. , Dailey (African Journal of Education,Science and Technology (AJEST), 2017)
The aim of the study was to determine the potential risk posed by meat and unprocessed milk in the transmission of Brucellosis to humans in Eldoret Municipality. The study was longitudinal using simple random sampling. A total of 1085 milk and 928 serum samples were collected. Brucella milk ring test (MRT) and Rose Bengal Plate Test (RBPT) were performed on the milk and serum samples respectively. Compliment Fixation Test (CFT) was carried out as a confirmatory test at the Central Veterinary Laboratories in Nairobi on all the serum samples. All the bovine samples were negative for Brucellosis on both RBPT and CFT. Five of the 245 samples (2.0%) from goats were positive on CFT. One of the 152 (0.7%) serum samples from ovine was positive for Brucella abortus antibodies in both RBPT and CFT. Bulking of milk at collection points could have led to high levels of dilution interfering with the sensitivity of the tests. Moi Teaching and Referral Hospital (MTRH) records had 48 out of 41198 (0.1%) patients positive for Brucella melitensis. Records at the Regional Veterinary Investigation Laboratory (RVIL) in Eldoret, showed that Brucellosis accounted for 1% (2001) and 2% (2002) of all cases handled in the laboratory. Brucellosis prevalence in meat (sera) and milk in the study area was negligible consequently; transmission to man through consumption of meat and milk may be negligible. The low prevalence of bovine brucellosis requires constant surveillance in case the prevalence may change.